Enhancing Creative Arabic Language Production For Advanced C1 And C2 Learners Using Fictional Literary Texts: A Study Aligned With The CEFR - Boulaares, Djemai Mahmoud; Al-Dubayan, Ibrahim bin Ali bin Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research explores the role of Arabic literary fiction in enhancing advanced non-native learners’ creative language production at CEFR levels C1 and C2. By engaging 40 advanced students from diverse linguistic backgrounds in a 12-week structured intervention, the study aims to strengthen creative Arabic writing skills through extensive literary analysis and critique training. Utilising both quantitative and qualitative approaches, the study will analyse the impact of literary engagement on vocabulary expansion, expressive accuracy, and cultural understanding. Quantitative analysis will be conducted using SPSS to evaluate students' writing development, while NVivo will assist in examining linguistic nuances and expressive patterns in their written output. Preliminary expectations suggest regular interaction with fictional texts will improve students' lexical and structural complexity and deepen their cultural insight. This approach could guide future pedagogical frameworks, particularly in advanced Arabic language courses, by integrating creative writing with literary analysis.